The Cultural role of woman in Sulaymaniya City (1975_1990) (Raparin Journal of Humanities (RJH), 2023)
This paper entitled ""The Cultural role of woman in Sulaymaniya City 1975_1990"" aims to introduce the role of woman in Sulaymaniya and analyze it through a scientific methodology. Years between 1975_-1990 is considered as an important stage in the history Sulaymaniya since many activities have been till the present time. Moreover Sulaymaniya at that period of time was developing socially, intellectually, and culturally. Furthermore, women were practicing new ideologies and practicing new concepts of freedom which made woman's feeling compared to the other areas in Kurdistan wider. The reason for this shifting beside the pervious mentioned reasons; is that people were more open minded .Therefor, the existence of ,many women figures who broke the traditional norms of life had a great influence on the forms of thinking; among those were the talented writers. University, institution, journals, and the musical groups widened the space for women and enabled them to ride their horses. The establishment Sulaymaniya high school's musical group was the start point for women to practice their freedom and participate in artistic activities.